APLIKASI MANAJEMEN APOTEK (GoApotheca) MENGGUNAKAN METODE FIFO BERBASIS WEBISTE PADA APOTEK MOMONA BETUNG - Putri, Hilda Muslia; Ariati, Nining; Saluza, Imelda (Jurnal Ilmiah Informatika Global, 2025)
Momona Betung Pharmacy is a pharmacy located on Jl. Raya Betung - Jambi Ward I RT.004 RW.002 Betung District, Banyuasin Regency, which focuses on public health services, especially in selling medicines for adults and children. Momona Betung Pharmacy experiences problems in managing drug supplies because the system used is still conventional. The main problems include difficulties in monitoring real-time drug stocks, inaccuracies in recording expiration dates, slow information retrieval processes, and inefficiencies in reporting. This research is intended to create a website-based pharmacy management platform called GoApotheca by implementing the FIFO method to overcome this problem. The FIFO method was chosen to ensure drug quality by arranging sales based on the first items received. This system was prepared and developed using the Agile method, with design using UML, and utilizing the PHP and MySQL programming languages as a database for data storage, where testing of this system was carried out using the black box testing method. The results of this research indicate that a computerized system can increase the effectiveness of managing drug supplies, speed up transactions, increase recording accuracy, and provide the public with the latest information about pharmacies. It is hoped that with this website-based GoApotheca application, the Momona Betung Pharmacy management system can become more structured, accurate and efficient.